Statut et tendances des effectifs d'éléphants dans les aires protegées de l'Est du Burkina Faso - Philippe Bouché; Clark Lungren; Leonard Ouedraogo (Pachyderm)
Discusses results of aerial surveys 26 April - 3 May 2000 in Arly NP and vicinity including the Pama Complex and the Singou, Ouamou areas and compares these to other surveys and population reviews undertaken over the past decade. The present estimate of a possibility of almost 2400 (1743 =/- 648 at 95% confidence) is sufficiently close to Barnes' 1999 estimate of about 2000 to be considered accurate. The distribution noted in this survey was similar to that noted by Barnes during the wet season. Between 1982 and 1992 there was a significant amount of poaching in this area, but within the past ten years the situation has improved. It is suggested that 200-300 animals came from Togo between 1990 and 1993. The relatively large and interconnected protected areas in this region bode well for maintainence of the savannah elephant population. Poaching in the region appears to be limited. The surveyed area in southwestern Burkina Faso in the vicinity of Arly NP probably supports the largest savannah elephant population in West Africa.